THE EFFECT OF STUDENTS’ MOTIVATION IN THE ESP CLASSROOM THROUGH LEARNING ENGLISH ACHIEVEMENT ON STUDENTS’ COMPUTER SCIENCE - Ida Maulida; Mimin Aminah; Virgiananda Sucinur Hermawan (LPSDI Bina Patria, 2023)
This research presents the results of the experiment method with the design by using one group pre-post-test design. The purpose of this study is to determine that students comprehend and interpretative the material in learning English for Specific Purposes (ESP). The results and discussion in the form of descriptive consists of 53 students in computer science learning English. Meanwhile, data collection techniques were carried out by observation and questionnaire. All students responded positively to the program. It is to stimulate their opinions, ideas, issues, and abilities or skills all the while encouraging them in learning a variety of English-related topics. The research to know (1) the effect of student motivation on students’ computer science in learning English achievement (2) the computer students' English material needs related to the “English for Computer Science” or students' analysis needs on students’ computer science. In other words, the English learning material in Students’ Computer Science improves students’ motivation in EFL learning and is regarded to be efficient and can enhance overall student learning outcomes.